Australia’s wish list of exotic pets: biosecurity and conservation implications of desired alien and illegal pet species - Adam Toomes; Oliver C. Stringham; Lewis Mitchell; Joshua V. Ross; Phillip Cassey (NeoBiota, 2020)
Globalisation of the live pet trade facilitates major pathways for the transport and introduction of invasive alien species across longer distances and at higher frequencies than previously possible. Moreover, the unsustainable trade of species is a major driver for the over-exploitation of wild populations. Australia minimises the biosecurity and conservation risk of the international pet trade by implementing highly stringent regulations on the live import and keeping of alien pets beyond its international CITES obligations. However, the public desire to possess prohibited alien pets has never been quantified and represents a number of species that could be acquired illegally or legally under different future legislative conditions. As such, highly desirable species represent an ongoing conservation threat and biosecurity risk via the pet-release invasion pathway. We aimed to characterise the Australian desire for illegal alien pets and investigate potential sources of external information that can be utilised to predict future desire. Using public live import enquiry records from the Australian Commonwealth Department of Agriculture, Water and the Environment as a proxy for alien pet desire, we tested for differences in the proportion of species with threatened listings and records of invasions, after accounting for taxonomy. Additionally, we used a United States of America (U.S.) live imports dataset to infer pet demand in another Western market with less stringent regulations and determined whether species highly desired in Australia had higher U.S. trade demand than would be expected by chance. The Australian public desire for alien pets is heavily and significantly biased towards species threatened with extinction, species popular in the U.S. trade and species with a history of successful invasions. Not only does this indicate the potential impacts of pet desire on invasion risk and the conservation of threatened species, but we also highlight the potential role of the U.S. trade as an effective predictor for Australian desire. Our research emphasises the value of novel datasets in building predictive capacity for improved biosecurity awareness.